2015
DOI: 10.1007/s11160-015-9403-0
|View full text |Cite
|
Sign up to set email alerts
|

High-grading and over-quota discarding in mixed fisheries

Abstract: High-grading is the decision by fishers to discard fish of low value that allows them to land more valuable fish. A literature review showed high-grading is reported in commercial and non-commercial fisheries around the world, although the number of observations is small. High-grading occurs in fisheries that are restricted to land their total catch due to management, market or physical constraints. Using the mixed flatfish fishery as a model system, a dynamic state variable model simulation showed that high-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 95 publications
2
41
0
2
Order By: Relevance
“…Evidence of high‐grading was also found by Batsleer et al. () in 44 out of 336 papers containing onboard observations, interviews, or self‐reported logbook data. The authors determined that high‐grading is likely underreported in many fisheries due the difficulty in detecting discards and could potentially undermine the sustainable management of many fish stocks.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Evidence of high‐grading was also found by Batsleer et al. () in 44 out of 336 papers containing onboard observations, interviews, or self‐reported logbook data. The authors determined that high‐grading is likely underreported in many fisheries due the difficulty in detecting discards and could potentially undermine the sustainable management of many fish stocks.…”
Section: Discussionsupporting
confidence: 60%
“…Early analyses of trip limits in the U.S. West Coast groundfish fishery by Pikitch et al (1988) found evidence of high-grading and that the discard rate had an inverse relationship when compared with the magnitude of the trip limit imposed. Evidence of high-grading was also found by Batsleer et al (2015) in 44 out of 336 papers containing onboard observations, interviews, or self-reported logbook data. The authors determined that high-grading is likely underreported in many fisheries due the difficulty in detecting discards and could potentially undermine the sustainable management of many fish stocks.…”
mentioning
confidence: 84%
“…This suggests that the commercial multispecies gill-net fishery imparts substantial mortality even when the Striped Bass harvest season is closed. The reason for this mortality is obscure, but it may be attributable to dead discard mortality; over-quota and high-grading mortality; avoidance, predation, and drop-out mortality; or unreported, misreported, and illegal harvest (ICES 1995;Gilman et al 2013;Batsleer et al 2015;Uhlmann and Broadhurst 2015). In particular, discard mortality should be carefully considered, as Clark and Kahn (2009) found that Striped Bass are acutely susceptible to discard mortality in multispecies gill-net fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we consider discards that arise from target stocks that are subject to single species assessments rather than bycatch of unwanted species. A related intermediate process is "high grading" where quota or vessel capacity limits lead to only the more valuable size classes being retained even though smaller fish may be legally landed or have a market value (Batsleer, Hamon, Overzee, Rijnsdorp, & Poos, 2015). We refer to these two elements as "size" or "bulk" discarding (Heath & Cook, 2015).…”
Section: Cookmentioning
confidence: 99%
“…We refer to these two elements as "size" or "bulk" discarding (Heath & Cook, 2015). A related intermediate process is "high grading" where quota or vessel capacity limits lead to only the more valuable size classes being retained even though smaller fish may be legally landed or have a market value (Batsleer, Hamon, Overzee, Rijnsdorp, & Poos, 2015).…”
Section: Introductionmentioning
confidence: 99%